2010
DOI: 10.1002/mrm.22267
|View full text |Cite
|
Sign up to set email alerts
|

MultiexponentialT2, magnetization transfer, and quantitative histology in white matter tracts of rat spinal cord

Abstract: Quantitative MRI measures of multiexponential T 2 relaxation and magnetization transfer were acquired from six samples of excised and fixed rat spinal cord and compared with quantitative histology. MRI and histology data were analyzed from six white matter tracts, each of which possessed unique microanatomic characteristics (axon diameter and myelin thickness, in particular) but a relatively constant volume fraction of myelin. The results indicated that multiexponential T 2 relaxation characteristics varied su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
165
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(186 citation statements)
references
References 40 publications
(62 reference statements)
20
165
1
Order By: Relevance
“…Our most striking findings in this study, perhaps, is that µFA DODE showed an extremely high, and statistically significant, negative correlation with axon diameters reported by Dula et al [75] and Harkins et al [98] for the different tracts ( Table 3). This observation lends further credence to the explanation above: the finite parallel length scale probed by DODE makes the measurement strongly dependent on the perpendicular restriction, which in this case is reflected through axon sizes.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Our most striking findings in this study, perhaps, is that µFA DODE showed an extremely high, and statistically significant, negative correlation with axon diameters reported by Dula et al [75] and Harkins et al [98] for the different tracts ( Table 3). This observation lends further credence to the explanation above: the finite parallel length scale probed by DODE makes the measurement strongly dependent on the perpendicular restriction, which in this case is reflected through axon sizes.…”
Section: Discussionsupporting
confidence: 67%
“…Extracellular space contributions again cannot be neglected here, but for coherently aligned systems the arguments are similar as one could potentially treat the space between densely packed axons as potentially even more restricted than the intra-axonal space itself [45]. It is also worth mentioning that MWF extracted from multiexponential T 2 measurements, as performed in this study, have been shown in the past to reflect microstructural metrics such as axon size and myelin thickness very faithfully in white matter [67,75,97].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For example, if the tissue of interest has a low T2 relaxation time before contrast administration (e.g., liver), resolving the concentration of the two agents may be problematic due to excessive T2 decay. In addition, in vivo studies may be impacted by multiple factors including partial volume effects, flow effect, and magnetization transfer and/or chemical exchange that may benefit from multi-exponential relaxation models instead of the simple mono-exponential models used here 44,45 . Despite these challenges, DC-MRF offers a unique opportunity to expand the portfolio of in vivo contrast-enhanced MRI applications.…”
Section: Discussionmentioning
confidence: 99%
“…Although MWF mapping was particularly noisy when it was first introduced (MacKay et al, 1994), relatively good quality MWF maps can now be obtained rapidly (Deoni et al, 2008;Oh et al, 2013;Prasloski et al, 2012). qMT generates maps with similar noise level as MWF (depending on acquisition time), but with particularly small contrast in the white matter (Dula et al, 2010;Levesque et al, 2010). Proton density maps are highly detailed with relatively good quality and correlate with qMT and MWF (Mezer et al, 2013).…”
Section: Qualitative Assessmentmentioning
confidence: 99%